Development of nanocomposite chitosan films with antimicrobial activity from agave bagasse and shrimp shells - Montes de Oca-Vásquez, Gabriela (2023)
In this study, the nanocomposite chitosan films with antimicrobial activity from agave bagasse and shrimp shells were developed. Chitosan was successfully extracted from shrimp shells waste and cellulose nanofibers were obtained from bagasse agave. To improve the antimicrobial activity, different silver nanoparticle concentrations (2.5, 5, and 10% v/v) were added in the formulation. The films were prepared using the solvent casting technique and the film samples were characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis, and scanning electron microscopy. The functional properties were also evaluated, including transparency, antibacterial activity (against Escherichia coli), water-solubility, swelling, and mechanical properties. The moisture content and water solubility decreased when the silver nanoparticles and nanofiber were added to the films. An increase in strength and modulus was determined when the nanofibers were added to the film. and with the addition of silver nanoparticles a decrease of the mechanical properties proportional to the nanoparticle content was observed. Therefore, there was an increase in the mechanical properties of chitin films with the incorporation of nanofibers and the addition of 2.5% and 5% of silver nanoparticles. Chitosan/nanofiber-based films displayed a total antibacterial activity against E.coli compared to chitosan-based films, with a synergistic effect between chitosan and cellulose nanofibers. This work highlights the potential of chitosan films reinforced with nanofibers and silver nanoparticles to act as green alternative for food preservation and packaging.